Wage Controls and Employment in a Socialist Economy - Lane, Timothy (IMF Working Papers; Working Paper ;, 1991)
Wage controls have been an important element of several of the stabilization programs recently introduced in reforming socialist economies. In some cases, the controls have been placed on each state enterprise's total wage bill, rather than on the wage rate paid. Such an incomes policy would be expected to have a dampening effect on employment, but this has not generally occurred; on the contrary, declines in employment in state enterprises have typically been much less than the associated declines in output. This paper presents a simple model of a labor-managed enterprise which offers an explanation of the behavior of wages and employment under such an incomes policy.